Humanizing Islamic Religious Education in Bali During the Covid-19 Pandemic - Ramdhani, Fajri Zulia; Rusmayani, Rusmayani; Kurniawati, Kurniawati (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2021)
AbstractThe delivery of Islamic Religious Education (PAI) in Bali has been fraught with difficulties, which have been exacerbated by the pandemic. This paper discusses 1) the realities of Islamic religious education in Bali, 2) the implementation of a special condition curriculum as a means of humanizing PAI education, and 3) the humanization of Islamic religious education in Bali during the COVID-19 pandemic. This research employed a qualitative phenomenological study, with data gathered through in-depth interviews with school principals, Islamic Religious Education teachers, and Muslim students' parents. The data is handled in stages that include data reduction, visualization, and verification. The findings indicate that: 1) The ratio of Islamic Religious Education teachers to pupils is imbalanced; some schools even lack Islamic Religious Education teachers, and numerous parents express dissatisfaction with online learning in PAI sessions. 2 ) Curriculum implementation for special/emergency situations; some schools have implemented it as a means of increasing learning effectiveness and efficiency, while others continue to use the national curriculum, despite teacher recognition that it is unproductive. 3) The special education curriculum is considered one of the first steps toward humanizing Religious Education Islam, which, in the face of poor online learning, must also be accompanied by teachers who are accessible to parents and students. AbstrakPenyelenggaraan Pendidikan Agama Islam (PAI) di Bali penuh dengan kesulitan yang diperparah dengan adanya pandemi. tujuan dari penelitian ini adalah untuk menyelidiki penggunaan kurikulum pengaturan khusus/darurat sebagai metode memanusiakan pendidikan. Tulisan ini membahas 1) realitas pendidikan agama Islam di Bali, 2) penerapan kurikulum kondisi khusus sebagai sarana memanusiakan pendidikan PAI, dan 3) humanisasi pendidikan agama Islam di Bali pada masa pandemi COVID-19. Penelitian ini menggunakan studi kualitatif fenomenologis, dengan data dikumpulkan melalui wawancara mendalam dengan kepala sekolah, guru Pendidikan Agama Islam, dan orang tua siswa Muslim. Penanganan data dilakukan secara bertahap yang meliputi reduksi data, visualisasi, dan verifikasi. Hasil penelitian menunjukkan bahwa: 1) Rasio guru PAI terhadap siswa tidak seimbang; beberapa sekolah bahkan kekurangan guru PAI, dan banyak orang tua menyatakan ketidakpuasan dengan pembelajaran online di sesi PAI. 2) Implementasi kurikulum untuk situasi khusus/darurat; beberapa sekolah telah menerapkannya sebagai sarana untuk meningkatkan efektivitas dan efisiensi pembelajaran, sementara yang lain tetap menggunakan kurikulum nasional, meskipun diakui oleh guru bahwa kurikulum tersebut tidak produktif. 3) Kurikulum pendidikan luar biasa dianggap sebagai salah satu langkah awal untuk memanusiakan Pendidikan Agama Islam, yang dalam menghadapi pembelajaran online yang buruk, juga harus didampingi oleh guru yang dapat diakses oleh orang tua dan siswa.How to Cite: Ramdhani, F. Z., Rusmayani, Kurniawati. (2021). Humanizing Islamic Religious Education in Bali During the Covid-19 Pandemic. TARBIYA: Journal of Education in Muslim Society, 8(1), 66-81. doi:10.15408/tjems.v8i1.20636.